'How did you find the argument?': Conflicting discourses in a master's dissertation tutorial (UCL Press, 2017)
This paper discusses feedback for developing L2 writing. It presents data from a serendipitous audio-recording of one L2 master's student's tutorial with her dissertation supervisor at a UK university, which is extracted from a 13-month linguistic ethnography. Following 'academic literacies' scholars, I view the tutorial as a 'literacy event' (Heath, 1982: 83), which, I argue, takes place in a 'backstage' (Goffman, 1959) social learning space where student-teacher power relations and identities may be asymmetrical, contested, and fluid. In line with the tenets of linguistic ethnography (Copland and Creese, 2015: 13), the discourse analysis of the tutorial considers how the interaction here is 'embedded in wider social contexts and structures'. I identify dominant institutional discourses and discuss how these create power relations that interact with language, identities, and agency in the student's experience. These data are triangulated with post-recall interviews with the two participants, the dissertation draft with the lecturer's written feedback, the summative feedback, and course documents. Findings demonstrate that, while the student was interested in developing argumentation, the supervisor focused on other aspects. I relate this to recent literature on knowledge transformation and argumentation in academic writing, and discuss its implications for L2 master's students by drawing on Bourdieu's notion of 'right to speak' (1991).